JUDICIAL REVIEW PASAL-PASAL MAKAR KUHP: PERSPEKTIF PENAFSIRAN HUKUM DAN HAM (JUDICIAL REVIEW ON TREACHERY ARTICLES OF THE CRIMINAL CODE: THE PERSPECTIVE OF LAW INTERPRETATION AND HUMAN RIGHTS) - Prianter Jaya Hairi (Pusat Penelitian Badan Keahlian Setjen DPR RI, 2017)
In 2017, Constitutional Court has received three calls for judicial reviews regarding treachery (makar) article in the Criminal Code. These articles deemed to be contradicting with the principle of legal certainty and freedom of expression. This study analyzes the important issue that is being debate in those judicial reviews. One of those is about the argument which says that the absence of the definition of treachery in the Criminal Code has caused a violation of legal certainty. Besides, the rule of treachery in the Criminal Code has also considered to have caused a violation of freedom of expression which has been guaranteed by Constitution. Analysis shows that the absence of treachery definition in the Criminal Code is not something that instantly becomes a problem in its application that causing the loss of legal certainty. Law enforcer, especially judge, in enforcing the rule of law must always use the method of law interpretation which appropriate with legal norm. With systematic interpretation, treachery can be interpreted according to the sentence of the rule as a unity of the legal system. In this case, the term treachery as regulated in Article 87 of the Criminal Code can be systematically interpreted as the basis for Article 104-Article 108 of the Criminal Code, Article 130 of the Criminal Code, and Article 140 of the Criminal Code which regulates various types of treason and their respective legal sanctions for the perpetrators. Further, on the argument that the articles of treachery in the Criminal Code also can not necessarily be said to limit the freedom of expression, because every citizen’s freedom has limitation, including the limitation of law and human rights. AbstrakPada tahun 2017, Mahkamah Konstitusi telah menerima tiga kali judicial reviewterhadap pasalpasal tindak pidana makar dalam Kitab Undang-Undang Hukum Pidana (KUHP). Pasal-pasal ini dipandang bertentangan dengan prinsip kepastian hukum dan kebebasan berekspresi. Tulisan ini menganalisis substansi yang menjadi perdebatan dalam perkara judicial review tersebut. Di antaranya perdebatan mengenai tidak adanya definisi istilah makar dalam KUHP yang menyebabkan persoalan kepastian hukum. Selain itu, pengaturan tindak pidana makar dalam KUHP juga dinilai melanggar kebebasan berekspresi yang telah dijamin oleh konstitusi. Analisis terhadap persoalanpersoalan tersebut menunjukkan bahwa ketiadaan definisi kata “makar” dalam KUHP bukanlah merupakan sesuatu yang serta merta langsung menjadi persoalan dalam penerapannya sehingga menyebabkan hilangnya kepastian hukum. Penegak hukum, terutama hakim, dalam menegakkan peraturan hukum selalu menggunakan metode penafsiran hukum yang sesuai dengan kaidah ilmu hukum. Dengan penafsiran sistematis, makar dapat dimaknai sesuai kalimat dari peraturan sebagai suatu kesatuan sistem hukum. Dalam hal ini, istilah makar yang diatur dalam Pasal 87 KUHP, secara sistematis dapat ditafsirkan sebagai dasar bagi Pasal 104-Pasal 108 KUHP, Pasal 130 KUHP, dan Pasal 140 KUHP yang mengatur tentang jenis makar beserta sanksi hukumnya masing-masing bagi para pelakunya. Selain itu, mengenai argumen bahwa pasal-pasal makar dalam KUHP berpotensi melanggar HAM dan dipandang bertentangan dengan konstitusi dapat dikatakan tidak beralasan. Sebab kebebasan HAM setiap orang tidak tanpa batas, di antaranya dibatasi nilai-nilai agama, keamanan, dan ketertiban umum.